In Utero Exposure to Phthalates and Fetal Development - LATINI, Giuseppe; DEL VECCHIO, Antonio; MASSARO, Marika; VERROTTI, Alberto; FELICE, Claudio DE (Current medicinal chemistry, 2006)
The diesters of benzene-1,2-dicarboxylic (phthalic) acid, commonly known as phthalates, are a family of industrial compounds, primarily used as plasticizers in enormous quantities for a variety of industrial uses in the formulation of plastics. Di-(2-ethylhexyl) phthalate (DEHP) is the most commonly used plasticizer. These plasticizers are not covalently bound to the polymer and leach out into the environment, thus becoming ubiquitous environmental contaminants. Cumulating evidence points out on the adverse effects of phthalate exposure during intrauterine life. Recently, it has been documented that in utero phthalate exposure is associated with a shorter duration of pregnancy. Phthalates induce and activate a subset of peroxisome proliferator-activated receptors (PPARs) and have an intrinsic pro-inflammatory activity, while some natural PPAR agonists induce cyclooxygenase (COX)-2 expression. To this regard, COX-2 is thought to be overexpressed in chorioamnionitis (CA), a fetal systemic inflammatory response syndrome and a leading cause of preterm birth. An adequate maternal dietary intake of essential fatty acids, well known antiinflammatory agents, is indispensable to fetal development. Recently, it has been shown that phthalates alter the placental essential fatty acids (EFAs) homeostasis so potentially leading to abnormal fetal development. Likewise, a possible down-regulation of COX-2 by omega-3 fatty acids has been suggested. As a consequence, maternal supplementation with omega 3 during pregnancy could counteract the adverse effects of phthalates exposure in the human fetus. Here, we analyze the existing evidence on the link between antenatal phthalate exposure and abnormal fetal development, as well as on possible therapeutic tools to fight the adverse effect of this exposure.